USING TASK-BASED APPROACH IN IMPROVING BENINESE EFL STUDENTS’ SPEAKING FLUENCY AND ACCURACY - TEBA, Corneille Sourou (My University, 2020)
This study works on using task-based Approach in Improving Beninese EFL Students’ Speaking Fluency and Accuracy. It shows how the exposure to the English language through Task-Based Approach is important for students’ speaking fluency and accuracy in Beninese Educational System. The methodology adopted is quantitative and qualitative. The investigation consists of collecting information from fourteen (14) teachers of English and six hundred and seventy (670) students of Ouémé region in Benin. Classroom observations have also been carried out. The results were presented in frequency and percentages through figures and tables. It reveals that the majority of teachers do not know much about the task-based approach. They do not use tasks which emphasize the exposure to language and this impact negatively students’ speaking. Some strategies are used to solve the problem of students’ speaking fluency and accuracy.
Keywords: EFL Students; Exposure; TBA; Speaking fluency; speaking accuracy